2021
DOI: 10.1093/ehjcvp/pvab005
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular effects of gonadotropin-releasing hormone antagonists in men with prostate cancer

Abstract: Aims The aim of this study was to determine whether gonadotropin-releasing hormone (GnRH) antagonists (an emerging class of drugs to suppress testosterone synthesis in the treatment of prostate cancer) cause less adverse cardiovascular events than the more commonly use GnRH agonists. Methods and Results We conducted a systematic review to identify all randomised, controlled trials in which a GnRH antagonist was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Additionally, the observational nature of this study predisposed to residual and unmeasured confounders. Specifically, some studies have suggested that gonadotropin-releasing hormone agonists and antagonists may differ in the risk of MACEs [32] , although this has remained highly controversial following the publication of the PRONOUNCE trial, the first randomised controlled trial specifically designed to compare the cardiovascular safety of gonadotropin-releasing hormone agonists and antagonists, which found no significant difference in the risk of MACEs between these agents [33] . Moreover, cancer staging, histology, disease risk profile, and individual indications for specific treatment regimens were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the observational nature of this study predisposed to residual and unmeasured confounders. Specifically, some studies have suggested that gonadotropin-releasing hormone agonists and antagonists may differ in the risk of MACEs [32] , although this has remained highly controversial following the publication of the PRONOUNCE trial, the first randomised controlled trial specifically designed to compare the cardiovascular safety of gonadotropin-releasing hormone agonists and antagonists, which found no significant difference in the risk of MACEs between these agents [33] . Moreover, cancer staging, histology, disease risk profile, and individual indications for specific treatment regimens were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Cirne et al (22) in their recent meta-analysis included also other studies such as the CS35A trial where data are presented only in abstract, and the HERO trial with relugolix was used as GnRH antagonist (Shore NEJM 2020). This meta-analysis was focused on CVD rates underlying that only in three out of ten randomized trials the prevalence of CVD at baseline was described.…”
Section: Impact Of Lhrh Agonists Versus Gnrh Antagonists In Terms Of CV Morbidity: Evidence From Randomized Trialsmentioning
confidence: 99%
“…Nonetheless, the objective within the urological community involved in the care of these patients, should be considered both scenarios with the intend of reducing OCM rates either at the time of RP and EBRT selection, based on OCM risk and/or susceptibility to ADT plus EBRT and ADT toxicity. [18][19][20][21][22][23][24] Fourth Our study has limitations and should firstly be interpreted in the context of its retrospective and population-based design. Secondly, no distinction could be made according to adjuvant or salvage EBRT after RP.…”
Section: 3%mentioning
confidence: 99%